Gender- and age-based analysis of emotional intelligence among badminton players in West Java clubs - Niko, Ade; Subroto, Toto; Hambali, Burhan (UIR Press, 2025)
Background: Although research on emotional intelligence (EI) continues to expand, limited studies have examined EI within the context of badminton, particularly from gender and age perspectives. Research Objectives: This study aims to analyze the emotional intelligence levels of badminton athletes in West Java by examining differences based on gender and age groups. Methods: A descriptive quantitative approach was employed, involving 50 participants (29 males and 21 females). Emotional intelligence was assessed using the emotional skills dimension of the Badminton Sport Life Skills Scale (LSSBS), developed by Hambali. Data were analyzed using descriptive statistics, independent samples t-tests, and one-way ANOVA, utilizing SPSS version 29.0. Finding/Results: The overall emotional intelligence level among participants was categorized as moderate (62%), with male athletes accounting for 38% and female athletes 24%. The t-test showed no statistically significant gender difference (p = 0.219), and the one-way ANOVA indicated no significant difference across age groups (p = 0.328). Conclusion: The findings suggest that emotional intelligence levels among badminton players in West Java do not significantly differ by gender or age. This study contributes to the existing literature by providing empirical evidence that can inform the development of targeted emotional intelligence training programs within badminton coaching contexts.